2021
DOI: 10.1093/ecco-jcc/jjab016
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Safety and Efficacy of Etrasimod for Ulcerative Colitis: Results from the Open-label Extension of the OASIS Study

Abstract: Background and Aims Etrasimod is an oral, selective, sphingosine 1-phosphate receptor modulator. In a phase 2, randomised, double-blind, placebo-controlled trial in adults with moderately-to-severely active ulcerative colitis (OASIS), etrasimod 2 mg provided significant benefit versus placebo and was generally well tolerated. This open-label extension (OLE) evaluated safety and efficacy of etrasimod for up to 52 weeks. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
43
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(47 citation statements)
references
References 18 publications
1
43
0
1
Order By: Relevance
“…At week 12, the clinical improvement (a change from the baseline in the three-component Mayo Clinic Score) was higher in patients treated with 2 mg of etrasimod compared with the placebo (difference, 0.99 points; 90% CI 0.30–1.68) as well as the endoscopic improvement (41.8% vs. 17.8% for the placebo; p = 0.003). In the open-label extension study including 118 patients receiving 2 mg of etrasimod daily up to week 52, 64% of patients had a clinical response, 33% had clinical remission, and 43% had an endoscopic improvement [ 102 ]. Patients who achieved a clinical response, clinical remission, or an endoscopic improvement at week 12 maintained the effect of the treatment with 85%, 60%, and 69% of patients with a clinical response, clinical remission, or an endoscopic improvement, respectively, at the end of treatment.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…At week 12, the clinical improvement (a change from the baseline in the three-component Mayo Clinic Score) was higher in patients treated with 2 mg of etrasimod compared with the placebo (difference, 0.99 points; 90% CI 0.30–1.68) as well as the endoscopic improvement (41.8% vs. 17.8% for the placebo; p = 0.003). In the open-label extension study including 118 patients receiving 2 mg of etrasimod daily up to week 52, 64% of patients had a clinical response, 33% had clinical remission, and 43% had an endoscopic improvement [ 102 ]. Patients who achieved a clinical response, clinical remission, or an endoscopic improvement at week 12 maintained the effect of the treatment with 85%, 60%, and 69% of patients with a clinical response, clinical remission, or an endoscopic improvement, respectively, at the end of treatment.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 60% of the patients experienced treatment emergent adverse events (TEAEs), the most common being worsening of UC (19%) and anemia (11%). When excluding patients with worsening of UC, 51% of the patients (46/91) experienced a TEAE and three patients experienced a serious adverse event [ 102 ].…”
Section: Resultsmentioning
confidence: 99%
“…A total of 22% of patients maintained steroid-free clinical remission. Thus, long-term use of etrasimod at a dose of 2 mg per day was safe and brought measurable benefits to the patients [28].…”
Section: Sphingosine-1-phosphate Receptor Modulatorsmentioning
confidence: 93%
“…The study showed that in patients with moderate to severe UC, 2 mg of etrasimod led to significant clinical and endoscopic improvement. Following completion of the OASIS study, patients had the option of continuing etrasimod 2 mg treatment for an additional 34-40 weeks as part of an open-label extension (OLE protocol) [28]. The study was conducted in 14 countries and 51 clinical sites.…”
Section: Sphingosine-1-phosphate Receptor Modulatorsmentioning
confidence: 99%
“…Current safety data show a favourable safety profile but are limited by a relatively small number of participants. 81 Currently, there are several ongoing phase III studies in severely active ulcerative colitis (NCT04706793, NCT03950232, NCT03996369, NCT04176588, and NCT03945188) and moderate-to-severe Crohn's disease (NCT04173273).…”
Section: Etrasimod (Apd-334)mentioning
confidence: 99%